2021
DOI: 10.1007/s11596-021-2475-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Washed Microbiota Transplantation to Treat Patients with Mild-to-Severe COVID-19 and Suspected of Having Gut Microbiota Dysbiosis: Study Protocol for a Randomized Controlled Trial

Abstract: Objective: Coronavirus disease 2019 (COVID-19) is often accompanied by gastrointestinal symptoms, which are related to gut microbiota dysbiosis (GMD). Whether washed microbiota transplantation (WMT) is an effective treatment for COVID-19 patients suspected of having GMD by restoring the gut microbiota is unknown. This study is designed to explore the efficacy and safety of WMT in COVID-19 patients suspected of having GMD. Methods: This is a randomized, multicenter, single-blind prospective study. COVID-19 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Some articles also evaluated the effect of probiotics on COVID-19 infection. The majority of the studies found the probiotics bene cial for COVID-19 patients' recovery [23,[30][31][32][33][34][35][36][37][38][39][40][41]. One study evaluated the positive e cacy of FMT (Fecal microbial transplantation) for COVID-induced GI upset [35].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some articles also evaluated the effect of probiotics on COVID-19 infection. The majority of the studies found the probiotics bene cial for COVID-19 patients' recovery [23,[30][31][32][33][34][35][36][37][38][39][40][41]. One study evaluated the positive e cacy of FMT (Fecal microbial transplantation) for COVID-induced GI upset [35].…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies included in our review assessed the effects of probiotic implementations on symptoms, morbidity, and mortality rates among COVID-19 patients [23,[30][31][32][33][34][35][36][37][38][39][40][41]. Probiotics are live microorganisms whose administration in su cient quantities has been demonstrated to ameliorate immune response, participate in metabolism, and balance the host microbiome [166,167].…”
Section: Probiotic Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the gut microbiota-targeted positive effects by means of probiotics on GI and clinical symptoms in COVID-19 patients [ 222 ], Wu and colleagues (2021) are currently undertaking a clinical trial to establish whether FMT can treat gut microbiota dysbiosis. In particular, they will assess FMT clinical efficacy on GI symptoms, COVID-19 status, recovery from the disease, the inflammatory response, the intestinal mucosal barrier function, as well the clearance time of SARS-CoV-2 from feces [ 223 ].…”
Section: Fecal Microbiota Transplantation In Human Diseasesmentioning
confidence: 99%